An effective flux scheme for hypersonic heating prediction of re-entry vehicles. (15th November 2018) - Sun, Di; Qu, Feng; Yan, Chao
Highlights: A new parameter free flux scheme for hypersonic heating predictions is proposed. This scheme is capable of obtaining physical solutions at low speeds. This scheme is robust against the shock anomaly at hypersonic speeds. This scheme is with a high level of accuracy in hypersonic heating predictions. Abstract: In this article, an effective computational method called TVM is proposed for the hypersonic heating prediction of the re-entry vehicles. Aimming at resolving the boundary layer accurately, the method adopted the splitting manner of the Toro and Vzquez's splitting procedure with an improved low-dissipation modification. Also, the method is robust against the shock anomaly in hypersonic flows. The detailed construction of the scheme is presented and a series of testcases are conducted to validate the performance of the newly developed scheme. Finally, the scheme is applied to the simulation of the hypersonic re-entry vehicles. Numerical results show its high performance in the prediction of the re-entry vehicles hypersonic heating load compared to the traditional methods.